2004
DOI: 10.1080/08039480410005963
|View full text |Cite
|
Sign up to set email alerts
|

The influence of childhood sexual abuse factors on women's health

Abstract: A history of childhood sexual abuse has been shown to be common among adult women, 15-30% in prevalence studies. The childhood sexual abuse variables taken into account are commonly age of onset, duration, abuse forms and relationship between the child and the perpetrator. Within the Department of Psychiatry at Lund University Hospital, 45 women with experiences of childhood sexual abuse were offered a 2-year long trauma-focused group therapy. Half of the women had been sexually abused during childhood in pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
3
15
0
2
Order By: Relevance
“…Zanarini and colleagues [58] found that the severity of reported childhood sexual abuse was significantly related to the severity of symptoms of borderline personality disorder (BPD), including impulsive and suicidal behaviors. A Swedish study found a significant relationship between age of onset of childhood sexual abuse and severity of psychiatric symptoms in general [59]. This study found that the most victims had not told anyone about the abuse for fear of not being believed [59].…”
Section: Duration Severity and Perpetrator Of Abusementioning
confidence: 91%
“…Zanarini and colleagues [58] found that the severity of reported childhood sexual abuse was significantly related to the severity of symptoms of borderline personality disorder (BPD), including impulsive and suicidal behaviors. A Swedish study found a significant relationship between age of onset of childhood sexual abuse and severity of psychiatric symptoms in general [59]. This study found that the most victims had not told anyone about the abuse for fear of not being believed [59].…”
Section: Duration Severity and Perpetrator Of Abusementioning
confidence: 91%
“…Autores fazem a observação que em 74,8% dos casos de violência o agressor é próprio marido da vítima e em 12,2% é o companheiro 8 . A história de abuso sexual, em estudos de prevalência na infância, mostrou ser mais comum entre meninas do que em meninos 9,10 .…”
Section: Introductionunclassified
“…Em Porto Alegre (RS), em um total de cinquenta casos analisados, houve apenas um caso de uma menina com idade de dois anos 18 . As consequências psicológicas da violência sexual tendem a se tornar mais graves após os sete anos, idade que a criança passa a compreender os valores morais e sociais relacionados ao sexo 21 .…”
unclassified
“…The proportion of sexually abused clients in mental health settings reporting abuse of over 10-years duration varies from 11% to 32% (Gold, Hill, Swingle, & Elfant, 1999;Lundqvist, Hansson, & Svedin, 2004;Steel, Sanna, Hammond, Whipple, & Cross, 2004). Sexual abuse of 10-years duration or more is associated with incest, rather than extra-familial abuse.…”
mentioning
confidence: 99%